Preparações de frutas Tribulus terrestris afetam os perfis químicos de HPLC e as atividades antioxidantes, lipoxigenase e inibidoras de α-glucosidase (Research, Society and Development, 2022)
Tribulus terrestris fruit has been used as a traditional and popular medicine for the prevention and treatment of several diseases, including sexual dysfunction, atherosclerosis and hypertension. The aim of this study was to evaluate the antioxidant, lipoxygenase and α-glucosidase inhibitory activities of an ethanol extract from Brazilian T. terrestris and its fractions sequentially partitioned into n-hexane, dichloromethane, ethyl acetate and n-butanol. The antioxidant capacities were determined by DPPH and ABTS scavenging free radicals, chelating metal ions, reducing power and total antioxidant activity by using phosphomolybdenum. High-performance liquid chromatography with diode array detection (HPLC-DAD) fingerprint analysis and quantitation of total phenolics were performed on the samples. The dichloromethane fraction showed the most complex HPLC-DAD chemical profile. The ethyl acetate and butanol fractions revealed the best phenolic compound and flavonoid recovery from T. terrestris. Concerning antioxidant activity, the ethyl acetate fraction presented better capacity for scavenging DPPH, ABTS and hydroxyl radicals, reductive power, total antioxidant capacity (TAC) and α-glucosidase inhibitory activity than the other fractions. These results correlated closely with the levels of phenolic compounds and flavonoids. The hexane fraction showed the best metal chelating power and lipoxygenase inhibitory activity. The anti-diabetic and anti-inflammatory potential of Brazilian Tribulus terrestris depend on the method of preparation.